8β-hydroxy-3-oxopimar-15-ene exerts anti-inflammatory effects by inhibiting ROS-mediated activation of the TRAF6-ASK1-p38 signaling pathway. (5th August 2013) - Cho, Jae-Heung; Lee, Jong Hyun; Lee, Eun-Jung; Nam, Dongwoo; Shim, Bum Sang; Song, Mi-Yeon; Kim, Sung-Soo; Kim, Sung-Hoon; Jung, Sang Hoon; Chung, Won-Seok; Ahn, Kwang Seok
Abstract: The flying squirrel's droppings ( Pteropus pselaphon ) have been used for improving the blood circulation, arresting bleeding to treat hematological disorders, and reducing pain. Here, 8β-hydroxy-3-oxopimar-15-ene (OXO), one of main constituents of P. pselaphon, was examined for its anti-inflammatory activity in murine macrophages. We found that OXO significantly suppressed LPS-induced nitric oxide (NO) without exerting cytotoxic effects on RAW 264.7 cells. OXO inhibited the expression of LPS-induced iNOS and COX-2 protein and their mRNA in a dose-dependent manner. Also, TNF-α, IL-6, and PGE2 secretion was decreased by OXO in LPS-stimulated macrophages. These inflammatory biomarkers were attributed to the suppression of LPS-induced activation of p38 MAPK and subsequent activation of two components of AP-1 (c-Jun and c-Fos), but not of ERK, JNK, NF-κB. Moreover, OXO inhibited LPS-induced intracellular reactive oxygen species (ROS) production and co-incubation of OXO and hydrogen peroxide (H2 O2 ) suppressed the phosphorylation of p38 in a concentration-dependent manner. In addition, OXO completely disrupted the formation of TRAF6-ASK complex in the cells. Therefore, we demonstrate here that OXO can potentially inhibit several biomarkers related to inflammation through inhibition of ROS-mediated activation of TRAF6-ASK1-p38 pathway.